COVID-19 AND MIGRANT WORKERS: A CONSPECTUS ON ASSESSING ACCOUNTABILITY AT THE HANDS OF THE GOVERNMENT IN INDIA - Moniga.S; Rao, B.Someswara (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The plight of migrant workers in India during COVID-19 pandemic is inextricably intertwined with legal and policy failure of systemic nature. This sudden imposition of lockdown in millions of people were deprived where thousands of migrant labours stuck with no jobs, no healthcare and no social security. A few weeks ago, Liz Murray posted a great article that critically examined the nature of government action and legal structures pertaining to migrant workers’ rights in the importance context of the pandemic. It assesses the gap between the existing labor laws, the court interventions and the policy responses — and implementation and accountability are examined against these benchmarks. It examines the obligations of the Indian government, under the Constitution and International Human Rights Law to protect the rights of migrants. This article attempts to assess the legal loopholes and possible reforms needed to protect the rights of migrant labourers by examining landmark cases, statutory instruments, and welfare measures of the state in the backdrop of the crisis. The results indicate that although certain measures were put in place to address hardships, these measures did expose migrant workers to long-term insecurity and injustice. The article ends with a call to reinforce labor legislation, the social protection mechanism, and accountability in crisis management.